PENERAPAN BIMBINGAN KELOMPOK DENGAN MENGGUNAKAN TEKNIK MODELING UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA UNDERACHIEVER - Putri, Resti Vidia; Rosita, Tita (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2019)
The purpose of this study was to determine the effect of group guidance services with modeling techniques on increasing learning motivation of underachiever students. The research method used is a quasi experiment. The population of this study were students of class XI MIPA who had an IQ of â‰¥ 130, totaling 30 students. The sampling technique used was purposive sampling and a sample of 13 students was obtained. The data collection method used was a psychological scale in the form of a learning motivation scale. The results showed that the students' motivation before being given the modeling technique group guidance service was in the low category with an average percentage of learning motivation of 45%. After being given guidance service the modeling technique group was in the high category with a percentage of 84% so that there was an increase of 39%. In addition, the data obtained through the Wilcoxon pairs match test with n = 13, 5% significance level obtained Tcount> Ttable (90> 21) or Ha was accepted and Ho was rejected. This means that group guidance with application modeling techniques has an effect on increasing learning motivation of underachiever students in class XI MIPA students of SMAN 1 Cisarua, West Bandung Regency, 2019/2020 academic year.Keywords:Â Motivation to learn, underachiever; group guidance, modeling techniques.